Africa's odious debts how foreign loans and capital flight bled a continent - Ndikumana, Léonce; Boyce, James K. (African arguments, 2011)
In Africa's Odious Debts, Boyce and Ndikumana reveal that, contrary to the popular perception of Africa being a drain on the financial resources of the developed world, more money destined for the West leaves the continent than it actually receives